INVENTARISASI JENIS FLORA DI PESISIR WISATA MANGROVE BOTUDIDINGGA GORONTALO UTARA - Inda R. Umadji, Nur; Amalia Gobel, Siti; SM, Farid; R. Juramang, Risnayanti (Jurnal Biogenerasi, 2024)
The mangroves in Botudidingga Tourism have an area of ​​around 100 hectares. These mangroves consist of various types, including mangrove, api-api, and nipah. Mangroves in Botudidingga Tourism have an important role in preserving the environment, namely as a barrier to abrasion, a habitat for marine biota and natural resources. Mangroves in Botudidingga Tourism are spread along the coastline of Dambalo Village. The mangroves in North Gorontalalo are still beautiful and green, this is because the village government and the people of Dambalo Village have made various efforts to preserve mangroves, such as reforesting mangroves, issuing mangrove protection regulations, and increasing public awareness about the importance of mangroves. The research method is using the exploration method. The exploratory method can be carried out with a qualitative approach with the aim of understanding the phenomenon in depth. The definition focuses on research, place, population and samples/informants, main materials and tools, data collection techniques, and techniques. Researchers make direct observations and data is collected based on findings in the field.